2017
DOI: 10.1007/s00268-017-4187-0
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Breast Cancer: Private Patients Have Better Outcomes Than Public Patients

Abstract: The greatest impact on outcome was stage at presentation, but more aggressive therapy for each stage resulted in a trend to better outcome for private patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…13 Per capita spending in the public health care system is < 15% of that in the coexisting private system; BC survival differs significantly between the two. 14,15 National policy specifies that low- or no-cost cancer surgery, chemotherapy, radiotherapy, and endocrine therapy be available at tertiary-level public hospitals, but timely access to these treatments is inconsistent.…”
Section: Methodsmentioning
confidence: 99%
“…13 Per capita spending in the public health care system is < 15% of that in the coexisting private system; BC survival differs significantly between the two. 14,15 National policy specifies that low- or no-cost cancer surgery, chemotherapy, radiotherapy, and endocrine therapy be available at tertiary-level public hospitals, but timely access to these treatments is inconsistent.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies have found that women from low SES, racial minorities and LEP are less likely to receive this standard of treatment . Similar trends have been reported in the receipt of chemotherapy and hormonal therapy as well . These findings are particularly concerning given systemic therapy in breast cancer is associated with reduced risk of metastasis and improved overall survival .…”
Section: Discussionmentioning
confidence: 75%
“…Such a discrepancy was not observed in our cohort, and the public and private hospitals were equivalent in surgical treatment delivery. Another study in a similar setting observed significantly higher reconstruction rates following mastectomy in the private vs public hospital . At large, African American women are noted to have lower rates of reconstruction in comparison to Caucasian women.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations